Mister Exam

Other calculators

Integral of -(ln(x))/x-1/x-c dx

Limits of integration:

from to
v

The graph:

from to

Piecewise:

The solution

You have entered [src]
  1                      
  /                      
 |                       
 |  /-log(x)    1    \   
 |  |-------- - - - c| dx
 |  \   x       x    /   
 |                       
/                        
0                        
01(c+((1)log(x)x1x))dx\int\limits_{0}^{1} \left(- c + \left(\frac{\left(-1\right) \log{\left(x \right)}}{x} - \frac{1}{x}\right)\right)\, dx
Integral((-log(x))/x - 1/x - c, (x, 0, 1))
Detail solution
  1. Integrate term-by-term:

    1. The integral of a constant is the constant times the variable of integration:

      (c)dx=cx\int \left(- c\right)\, dx = - c x

    1. Integrate term-by-term:

      1. There are multiple ways to do this integral.

        Method #1

        1. Let u=log(x)u = \log{\left(x \right)}.

          Then let du=dxxdu = \frac{dx}{x} and substitute du- du:

          (u)du\int \left(- u\right)\, du

          1. The integral of a constant times a function is the constant times the integral of the function:

            udu=udu\int u\, du = - \int u\, du

            1. The integral of unu^{n} is un+1n+1\frac{u^{n + 1}}{n + 1} when n1n \neq -1:

              udu=u22\int u\, du = \frac{u^{2}}{2}

            So, the result is: u22- \frac{u^{2}}{2}

          Now substitute uu back in:

          log(x)22- \frac{\log{\left(x \right)}^{2}}{2}

        Method #2

        1. Let u=1xu = \frac{1}{x}.

          Then let du=dxx2du = - \frac{dx}{x^{2}} and substitute dudu:

          log(1u)udu\int \frac{\log{\left(\frac{1}{u} \right)}}{u}\, du

          1. Let u=1uu = \frac{1}{u}.

            Then let du=duu2du = - \frac{du}{u^{2}} and substitute du- du:

            (log(u)u)du\int \left(- \frac{\log{\left(u \right)}}{u}\right)\, du

            1. The integral of a constant times a function is the constant times the integral of the function:

              log(u)udu=log(u)udu\int \frac{\log{\left(u \right)}}{u}\, du = - \int \frac{\log{\left(u \right)}}{u}\, du

              1. Let u=log(u)u = \log{\left(u \right)}.

                Then let du=duudu = \frac{du}{u} and substitute dudu:

                udu\int u\, du

                1. The integral of unu^{n} is un+1n+1\frac{u^{n + 1}}{n + 1} when n1n \neq -1:

                  udu=u22\int u\, du = \frac{u^{2}}{2}

                Now substitute uu back in:

                log(u)22\frac{\log{\left(u \right)}^{2}}{2}

              So, the result is: log(u)22- \frac{\log{\left(u \right)}^{2}}{2}

            Now substitute uu back in:

            log(u)22- \frac{\log{\left(u \right)}^{2}}{2}

          Now substitute uu back in:

          log(x)22- \frac{\log{\left(x \right)}^{2}}{2}

      1. The integral of a constant times a function is the constant times the integral of the function:

        (1x)dx=1xdx\int \left(- \frac{1}{x}\right)\, dx = - \int \frac{1}{x}\, dx

        1. The integral of 1x\frac{1}{x} is log(x)\log{\left(x \right)}.

        So, the result is: log(x)- \log{\left(x \right)}

      The result is: log(x)22log(x)- \frac{\log{\left(x \right)}^{2}}{2} - \log{\left(x \right)}

    The result is: cxlog(x)22log(x)- c x - \frac{\log{\left(x \right)}^{2}}{2} - \log{\left(x \right)}

  2. Add the constant of integration:

    cxlog(x)22log(x)+constant- c x - \frac{\log{\left(x \right)}^{2}}{2} - \log{\left(x \right)}+ \mathrm{constant}


The answer is:

cxlog(x)22log(x)+constant- c x - \frac{\log{\left(x \right)}^{2}}{2} - \log{\left(x \right)}+ \mathrm{constant}

The answer (Indefinite) [src]
  /                                                  
 |                                         2         
 | /-log(x)    1    \                   log (x)      
 | |-------- - - - c| dx = C - log(x) - ------- - c*x
 | \   x       x    /                      2         
 |                                                   
/                                                    
(c+((1)log(x)x1x))dx=Ccxlog(x)22log(x)\int \left(- c + \left(\frac{\left(-1\right) \log{\left(x \right)}}{x} - \frac{1}{x}\right)\right)\, dx = C - c x - \frac{\log{\left(x \right)}^{2}}{2} - \log{\left(x \right)}
The answer [src]
oo - c
c+- c + \infty
=
=
oo - c
c+- c + \infty
oo - c

    Use the examples entering the upper and lower limits of integration.